40 active learning strategies for the inclusive classroom, grades K-5 - Green, Linda Schwartz; Casale-Giannola, Diane (Corwin, 2011)
“An excellent tool to help teachers help students, this book would be particularly useful within a professional learning community or in a mentoring setting.”—Jim Hoogheem, Retired PrincipalFernbrook Elementary School, Maple Grove, MN“This book got me excited to teach in an inclusive setting! The tips and directions will work with every child and will ensure that ALL students can learn in the same environment.”—Rachel Aherns, Instructional Strategist IWestridge Elementary School, West Des Moines, IAEngage all learners with research-based strategies from acclaimed educatorsResearch indicates that students of all ages and demographics benefit from active learning strategies. The challenge is translating what we know into what we do. Award-winning educators Linda Schwartz Green and Diane Casale-Giannola build that bridge with more than 40 easy-to-implement strategies for today's inclusive classroom. This practical guide includes: Field-tested practices that are easily adaptable to various grade levels and subjects; Vignettes that demonstrate how to apply today's brain-compatible strategies in the classroom; Tools for differentiating instruction to serve ALL students, including high-ability students, those with ADHD or learning disabilities, and English learnersGrounded in foundational research and educational literature, these strategies include directions for use, sample applications across content areas, and how-to's for groups and individuals. Teachers and administrators will find this comprehensive guidebook an indispensable at-your- fingertips resource for enhancing student engagement, furthering professional development, and increasing positive learning outcomes.